Deeply lonely in the borderland between childhood and adulthood - Experiences of existential loneliness as narrated by adolescents - Tide Garnow; Pernilla Garmy; Anna-Karin Edberg; Eva-Lena Einberg (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Background Adolescence is associated with different feelings and experiences that can negatively affect adolescents’ health and well-being. In the transition between childhood and adulthood, experiences of loneliness are common. A deep form of loneliness is described as existential loneliness. Studies among adults have shown that existential loneliness often arises in connection with transitions and is related to suffering, but may lead to positive experiences when acknowledged and addressed. Therefore, the aim of this study was to explore adolescents’ experiences of existential loneliness. Methods This was an exploratory-descriptive qualitative study based on narrative interviews with 16 adolescents (median age 17.5). The data were analysed inductively using qualitative content analysis. Findings Existential loneliness among adolescents was related to experiences of social exclusion and “in-betweenness”. To alleviate their suffering, the adolescents tried to avoid burdensome feelings and thoughts, and they chose between sharing or not sharing their inner lives with someone else. Conclusions It is important to support adolescents’ sense of belonging, and they may need assistance in dealing with existential loneliness, as well as with finding constructive and healthy ways of recuperating from the suffering. Professionals need knowledge of existential loneliness to promote adolescents’ existential health and well-being.